Sources of alkylbenzenes in Lower Cretaceous lacustrine source rocks, West African rift basins - Pedentchouk, N.; Freeman, K.; Harris, N.; Clifford, D.; Grice, Kliti (Elsevier, 2004)
We conducted molecular biomarker and compound-specific carbon isotope analyses of off-line pyrolyzates from lacustrine samples recovered by ONEZ-1 well (the Kissenda Formation) in the Gabon Basin and Well A (the Maculungo Formation) in the Kwanza Basin in West Africa. Pyrolyzates from ONEZ-1 well contain isotopically depleted 1,2,3,4-tetramethylbenzene (1,2,3,4-TetraMB; 26.1 to 29.4%) and 1,2,4-trimethylbenzene (1,2,4-TriMB; 26.4 to 29.7%), which are isotopically similar to aryl isoprenoids (29.9 and 31.2%) and b-carotane (28.5 to 31.3%) identified in the bitumen fractions. Pyrolyzates from 3 samples in the lower sections of Well A contain isotopicallyenriched 1,2,3,4-TetraMB (ca. 16%) and 1,2,4-TriMB (ca. 14%), consistent with an origin from diagenetic products of isorenieratene/chlorobactene biosynthesized by green sulfur bacteria (Chlorobiaceae). Pyrolyzates from five samples in the upper sections of Well A are characterized by the presence of intermediate carbon-isotope values of 1,2,3,4- TetraMB (20.7 to 22.8%) and 1,2,4-TriMB (19.3 to 21.2%) and isotopically enriched isorenieratane (ca. 14.5%). Off-line pyrolyzates from these lacustrine source rocks represent two distinct end members: 13C-depleted diagenetic products of b-carotene derived from a lacustrine algal source and 13C-enriched diagenetic products of isorenieratene/chlorobactene derived from green sulfur bacteria. Organic matter (OM) from ONEZ-1 well shows a significant proportion of algal biomass with a 13C-depleted composition. The presence of 13C-enriched biomarkers derived from carotenoids of Chlorobiaceae from samples in the lower part of Well A indicates the development of photic zone euxinia and a significant biogeochemical role of sulfur. In the upper section of Well A, the 1,2,3,4-TetraMB and 1,2,4- TriMB have 13C values indicative of contributions from both Chlorobiaceae and algae to the OM.